Comparative pathological changes in aflatoxin fed broilers infected with hydropericardium syndrome - SHIVACHANDRA, S B; SAH, R L; SINGH, S D; KATARIA, J M; MANIMARAN, K (The Indian Journal of Animal Sciences, 2014)
The effect of aflatoxin feeding and FAV serotype-4 infection on the pathogenesis of HPS in broiler chicks were studied singly and in concurrence. Chicks in combined group showed marked clinical signs, early onset of high mortality rate (56.66%), increased quantity of pericardial fluid, more conspicuous intranuclear inclusion bodies in hepatocytes, severe degree of degenerative changes in liver, heart, kidney’s and depletion of lymphocytes in spleen, thymus, bursae and caecal tonsils, were comparable to that in individual groups.